2015
DOI: 10.17221/8525-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific mRNA expression profiles of GDF9, BMP15, and BMPR1B genes in prolific and non-prolific goat breeds

Abstract: ABSTRACT:The tissue-specific mRNA expression profiles of GDF9, BMP15, and BMPR1B genes in goats were investigated. The mRNA expression of the genes was detected in prolific Jining Grey goats and non-prolific Liaoning Cashmere goats by reverse transcription polymerase chain reaction (RT-PCR) and quantitative real-time PCR. The results showed that GDF9 and BMPR1B were widely expressed in 20 tissues, while BMP15 gene was expressed exclusively in ovary and pituitary. The expression levels of GDF9 and BMPR1B genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…Sheep carrying the FecB mutation exhibit higher ovulation numbers [ 11 ], which may be the cause of the different litter sizes of sheep in the three FecB genotypes. Moreover, the expression differences in BMPR1B in non-ovarian tissues of the HPG axis of sheep of the three FecB genotypes were not consistent with the results from goat breeds [ 35 ]. We infer that the expression profile described above may have a species discrepancy or the different timings of the sampling may have influenced the results.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Sheep carrying the FecB mutation exhibit higher ovulation numbers [ 11 ], which may be the cause of the different litter sizes of sheep in the three FecB genotypes. Moreover, the expression differences in BMPR1B in non-ovarian tissues of the HPG axis of sheep of the three FecB genotypes were not consistent with the results from goat breeds [ 35 ]. We infer that the expression profile described above may have a species discrepancy or the different timings of the sampling may have influenced the results.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, some researchers have found that BMPR1B has no tissue-specific expression in whole tissues, and it was also shown to have a high expression level in the ovaries of the Jining Grey goat and Liaoning Cashmere goat, implying that it not only exerts a great influence on the process of bone formation, but also has a potential role in ovarian development and even in the process of reproduction. However, no significant difference in expression was shown between these two goat breeds, which suggested that the BMPR1B may not contribute to the high fecundity of goats [ 35 ]. Similarly, it has also been speculated that differences in reproductive performance may be ascribed to the structural differences in BMPR1B between Lezhi black and Tibetan goats [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of GAPDH gene expression served as an internal control. The quantitative real-time PCR data were calculated by the 2 -∆∆Ct method (Pan et al 2015). Amplified products were separated by electrophoresis on a 2% agarose gel and detected under UV light.…”
Section: Doi: 1017221/42/2016-cjasmentioning
confidence: 99%